Kinetics of dye removal using Fe3O4 nanoparticles and pulsed white-LED illumination - P Damrongsak; B Klongratog; S Hoomsuk; K Locharoenrat (My University, 2019)
Removal of dyes with the aid of photocatalytic nanomaterials illuminated with continuous-light sources has been given substantial attention in the recent years.In the present work we study the efficiency of dye degradation using some alternative photocatalytic nanoparticles under condition of pulsed illumination.Our specific purpose is to investigate the removal of rhodamine 6G dye basing on suspended Fe 3 O 4 solution.The experiments are carried out in the batch mode when the effect of the exposition time (ranging from 30 to 150 min) on the dye removal is examined under both continuous and pulsed white-LED illuminations.Different pulsed-light frequencies and duty cycles are tested.We estimate the concentration of rhodamine 6G in the mixed solution following from its absorption spectrum measured with a UV-Vis spectrometer and determine in this manner the percentage of dye removal.Our main conclusion is that Fe 3 O 4 nanoparticles enable removing efficiently the rhodamine 6G dye under pulsed white-LED illumination.In particular, more than 90% of the dye is removed when the duty cycle is equal to 25% and the frequency to 30 kHz.The equilibrium state of this process is achieved in about 60 min.
Keywords: White (mutation); TiO2 Photocatalysis and Solar Cells